2007
DOI: 10.1177/0020764007075011
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Incidents, Patient Flow and Nursing Workforce Variables on Acute Psychiatric Wards: The Tompkins Acute Ward Study

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 21 publications
(23 reference statements)
3
58
0
Order By: Relevance
“…Our previous work has shown an inverse relationship between the presence of regular nursing staff and violent incidents (Bowers, Allan, Simpson, Nijman, & Warren 2005a;Bowers, Nijman, Allan, Simpson, Warren, & Turner 2005c), as has that of others (Chou, Lu, & Mao 2002;Lanza et al 1994), and in surveys of staff or patients larger numbers are often seen as necessary to reduce levels of violence (FaganPryor et al 2003;Kumar, Guite, & Thornicroft 2001). However one other study has also reported a positive association between staffing numbers and patient aggression (Owen et al 1998).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous work has shown an inverse relationship between the presence of regular nursing staff and violent incidents (Bowers, Allan, Simpson, Nijman, & Warren 2005a;Bowers, Nijman, Allan, Simpson, Warren, & Turner 2005c), as has that of others (Chou, Lu, & Mao 2002;Lanza et al 1994), and in surveys of staff or patients larger numbers are often seen as necessary to reduce levels of violence (FaganPryor et al 2003;Kumar, Guite, & Thornicroft 2001). However one other study has also reported a positive association between staffing numbers and patient aggression (Owen et al 1998).…”
Section: Discussionmentioning
confidence: 89%
“…Adverse events can also cause significant distress for staff (and sometimes injuries) and are thought to contribute to low morale, high sickness, high staff turnover and high vacancy rates (Garcia et al 2005;Needham et al 2005b). Poor staffing levels result in more adverse incidents (Bowers et al 2005a) and the consequent reliance on temporary staff is expensive and linked with lower standards of care (Audit Commission 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of nidotherapy within secure settings, gaining the support of fl uctuating staff teams with regime and policy imperatives, was particularly challenging: this is clearly crucial, as many of this patient groups will fi nd themselves in secure settings, often for extensive periods of time. When staff in such units frequently change or are relatively uninvolved in the therapeutic care of those with antisocial behaviour, aggressive episodes tend to increase (Bowers et al, 2007): this is both a complication for, and a driver of, the adoption of nidotherapy, not only for patient benefi t, but as a vehicle for more meaningful engagement of staff in facilitative and collaborative treatment in inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of single and repeat incidents of self-harm showed that therapist contact (performing a psychosocial assessment) was associated with a significantly decreased risk for a repeat incident, suggesting that the therapist-patient relationship has a moderating influence on repeat self-harming incidents (15). Further, we know from adult psychiatric literature that an increased risk for suicide has been associated with the discontinuity of care from a significant professional (16,17). Children and adolescents are dependent on a stable therapist-patient relationship (18,19) for a positive treatment outcome.…”
Section: Introductionmentioning
confidence: 99%